Uprawnienia funkcjonariuszy służb mundurowych związane z rodzicielstwem: Rights of uniform service officers related to parenthood (Studia Prawnicze / The Legal Studies, 2015)
Unormowania pragmatyk służbowych regulujących status funkcjonariuszy służb mundurowych w niektórych kwestiach odwołują do stosowania przepisów prawa pracy. Ich przykładem są przepisy odsyłające do stosowania Kodeksu pracy w zakresie uprawnień związanych z rodzicielstwem. Analizę treści przepisów odsyłających oraz uprawnień związanych z rodzicielstwem przysługujących funkcjonariuszom warto jednak poprzedzić uwagami na temat ewoluowania zakresu tych uprawnień. Przepisy pragmatyk służbowych były istotnie nowelizowane, podobnie jak przepisy Kodeksu pracy, gdy chodzi o uprawnienia rodzicielskie. Przedmiotem analizy będą przepisy dziesięciu pragmatyk służbowych dotyczących funkcjonariuszy Policji, Straży Granicznej, Państwowej Straży Pożarnej, Służby Więziennej, Służby Celnej, Biura Ochrony Rządu, Agencji Bezpieczeństwa Wewnętrznego i Agencji Wywiadu, Centralnego Biura Antykorupcyjnego, Służby Kontrwywiadu Wojskowego oraz Służby Wywiadu Wojskowego oraz żołnierzy zawodowych. Service regulations which define employment of uniform service officers in regards to parental rights, predicts provisions which refer to applying the provisions of the Labour Code. It means that, the services regulations are not complete, and therefore application of provisions from other law systems is allowed.Another example of relations between a uniform service employment and the labour law, is introducing rules to service regulations which are similar (or identical) to a labour law. As previously mentioned, the amount of benefit payment during the leave related to childcare, has been regulated in the same way to they employees who take this kind of leave.Making officer’s status similar to employe’s status cause diverse consequences for officers. Some of them are more favorable to officers, for example parental rights. In this way, officers can benefit from these rights regardless of gender. Almost in the same way as employees, officers also have a right to additional maternity leave and childcare leave. Other changes, in relation to making officer’s status similar to employe’s status, cause however loss of service officers’ privileges, for example decreased pay during sick leave.